Public perception towards life insurance policy a case study in Kota Bharu Kelantan / Che Hazira Che Ab Ghani - Che Ab Ghani, Che Hazira (2012)
This paper studies the public perception towards life insurance policy. The focus of this paper is to identify the factors that affected public perception towards life insurance which are market reputation, public awareness and the benefits. For this purpose, the researcher used primary data, which is a structured questionnaire and has focused to the respondents’ residing in Kelantan. The data were analyzed using SPSS through the frequency analysis, factor analysis, reliability, and descriptive statistic. Thus, the finding from this study shows that public perception have relationship between market reputation, public awareness and the benefits